Descartes : a very short introduction - Sorell, Tom (Very short introductions, 2000)
Rene Descartes (1596-1650) had a short working life, and his output was small, yet his contributions to philosophy and science have endured. This book shows that Descartes was, above all, an advocate and practitioner of a new mathematical approach to physics, and that he developed his metaphysics to support his programme in the sciences.